Assessing the Compliance of Randomized Controlled Trials Published in Craniofacial Surgery Journals With the CONSORT Statement. Issue 1 (January 2019) - Borrelli, Mimi R.; Farwana, Reem; Andrew, Tom W.; Chicco, Maria; Abukhder, Munir; Mobarak, Dima; Thavayogan, Rachel; Agha, Riaz; Pidgeon, Thomas E.
Abstract : Background: Randomized controlled trials (RCTs) are gold standard assessments for healthcare interventions. The Consolidated Standards of Reporting Trials (CONSORT) statement was published to maximize RCT reporting transparency. The authors conducted a systematic review to assess current compliance of RCTs published within craniofacial surgery with the CONSORT statement. Methods: The Thomson Reuters Impact Factor Report 2016 was consulted to identify craniofacial surgery journals. PubMed was used to search for recent RCTs published within the 5 journals identified. Two independent researchers assessed each study for inclusion and performed data extraction. The primary outcome was compliance of each RCT with the CONSORT statement. Secondary outcomes were the pathology and interventions examined, impact factor, multi-versus-single center, number of authors, and publication date. Results: Eighty-six studies met the inclusion criteria, across which a median of 56% (range 33%–94%) applicable CONSORT items were reported. The 5 least reported items were: trial design (3a); registration number and name of trial registry (23); who generated random allocation sequences, enrolled participants, and assigned participants to interventions (10); sample size determination (7a); mentioning "randomized trial" in the title (1a). Conclusion: The compliance of craniofacial surgery RCTs with the CONSORT statement requires improvement. Areas in need are identified, and methods to improve reporting transparency, are discussed. Abstract : Supplemental Digital Content is available in the text